The Relationship Of Knowledge On The Perception Of Economic Development Zakat Based (PEZ) - Asnaini, Asnaini; Hilmi, M. Izdad (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2019)
This study aims to examine the relationship between knowledge about zakatalerts maal to the perception of economic development based on zakat funds. This research uses simple regression analysis. The study was tested on 30 respondents in the city of Bengkulu using two questionnaire models. Namely tests for knowledge and scale 1-5 for perception. From the results of the analysis note that the variables are positively related. The regression equation of X to Y is Y = 60.489 + 1,176X1.The implication of the results of this study is the importance of continuing BAZNAS socialization to increase public knowledge and understanding of zakat alerts and the need for concrete efforts from the government and related parties in improving the performance of the National Zakat Board (BAZNAS) to foster public trust in zakat management by institutions BAZNAS so that his perception of economic development based on zakat funds is getting better and optimistic.